The Language of Entitlement and Crisis of Legitimacy: A Critical Discourse Analysis of Indonesian Legislators’ Statements on Housing Allowance Controversy: Penelitian - Muhammad Tahir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In August 2025, Indonesia faced a legitimacy crisis after the House of Representatives (DPR) established a housing allowance of IDR 50 million per month for its members. Although billed as an administrative efficiency measure, this decision sparked controversy because legislators were deemed arrogant and impartial. This study used qualitative methods with Critical Discourse Analysis (CDA), combining Fairclough's model and Van Dijk's socio-cognitive framework. Five statements were analyzed: numerical normalization (Adies Kadir), legal legitimacy (Ahmad Sahroni), structural normalization (Nafa Urbach), minimization (Eko Patrio), and rights-based legitimacy (Uya Kuya). Data came from videos, national media, and social media content. Results showed all discourse strategies failed; statements were perceived as symbols of arrogance, greed, or incompetence. Career politicians were criticized for being technocratic and out of touch with the public, while celebrity politicians were mocked more for their entertainment credentials. The media labeled statements as arrogant or absurd, while memes amplified phrases such as